A LITERATURE STUDY OF RACIAL CAPITALISM AND REPRESENTATION IN R. F. KUANG’S YELLOWFACE - Rasya Putri Ramadina; Revanita, Rinda; Salsabilla Zahran Galuh Putri Subawati; Lieztya Beliana (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This research explores the intersection of racial capitalism and representation in R.F. Kuang’s novel Yellowface (2023), which offers a powerful critique of the publishing industry’s commodification of minority voices. This research investigates how capitalist structures shape the way racial and cultural of East Asian identities are represented, appropriated, and exploited in contemporary literary production. This research uses a qualitative approach with textual analysis as the main method, applying theories of racial capitalism, identity, and representation to examine the novel’s portrayal of power dynamics, performative allyship, and white fragility. The novel centers on June Hayward, a white author who steals a manuscript from her late Asian American friend, Athena Liu, and publishes it under an ambiguous pseudonym to benefit from the diversity trend. Through this act, Kuang critiques the exploitation of marginalized experiences by dominant (white) institutions and individuals in pursuit of profit and legitimacy. The analysis reveals several major issues: first, the fetishization of exotic cultural identity as a marketable commodity; second, the silencing of subaltern voices by dominant power structures; and third, the prevalence of symbolic diversity and superficial inclusion within the creative industries. This research concludes that Yellowface not only exposes how race and cultural trauma are used as tools for economic gain in the publishing world, but also challenges the ethical boundaries of authorship, authenticity, and allyship in a racially stratified capitalist system. The novel encourages readers and cultural institutions to reflect on how they may contribute to injustice while appearing to support inclusion and representation.